Peranan Guru Pendidikan Agama Kristen terhadap Pertumbuhan Iman Siswa Sekolah Dasar Bala Keselamatan Lempelero - Sarimin, Freliyanti (STT Bala Keselamatan Palu, 2023)
Abstract: Against the background of the lack of enthusiasm for student learning, and the lack of attention from the Christian religious education teacher to the learning of Christian religious education, which has been described, the problem is formulated; what is meant by the role of the christian religious education teacher, the way the christian religious education teacher carries out his role in the growth of student faith, as well as the role of the christian religious education teacher in the process of growing student faith. This study aims to determine the role of the Christian religious education teacher in the faith growth of grade III students and VI Lempelero Salvation Army elementary school. The method used in this research is qualitative. The samples taken were 15 students and 1 teacher. The results of the study show that the role of the Christian religion teacher can change the character of students' bad habitual behavior, such as; lazy to pray, do not like going to school during Christian religious education lessons to become Christian character and good behavior, students are more diligent in coming to school and like to pray and read the Bible before starting lessons, thus a Christian religious education teacher has the character of Christ, not only rather than transferring their knowledge, instilling their faith in Christ by guiding and directing and encouraging students at school. If this role is carried out properly, it will have a positive impact on the growth of students' faith. Abstrak: Dilatar belakangi oleh kurang semangat belajar siswa, dan kurangnya perhatian dari guru pendidikan agama Kristen terhadap pembelajaran pendidikan agama kristen, yang telah diuraikan maka dalam artikel ini membahas tentang klasifikasi guru Agama Kristen dalam mendidik Nara-didik, peran guru agama Kristen terhadap pertumbuhan Iman siswa, guru menjadi model yang dapat dicontoh, pembelajaran yang berdasarkan Alkitab, melakukan pembinaan rohani kepada nara didik. Penelitian ini bertujuan untuk mengetahui peranan guru pendidikan agama Kristen terhadap pertumbuhan iman siswa kelas III dan VI sekolah dasar Bala Keselamatan Lempelero. Metode yang digunakan dalam penelitian kualitatif. Sampel yang di ambil 15 orang siswa dan 1 orang guru. Hasil penelitian menunjukan bahwa peranan guru agama Kristen dapat mengubah karakter perilaku kebiasaan tidak baik siswa, seperti; malas berdoa, tidak suka ke sekolah pada jam pelajaran pendidikan agama Kristen menjadi karakter kristiani dan perilaku yang baik, siswa lebih rajin datang ke sekolah serta suka berdoa dan membaca Alkitab sebelum mulai pelajaran, dengan demikian seorang guru pendidikan agama Kristen memiliki karakter Kristus, bukan hanya mentransferkan ilmunya melainkan, menanamkan iman percaya mereka kepada Kristus dengan cara membimbing dan mengarahkan serta memberi semangat siswa di sekolah. Peran ini dilakukan secara baik maka akan memberi dampak positif bagi pertumbuhan iman siswa.